Proceedings of the 2014 International Conference on Physics and Its Applications 2014
DOI: 10.2991/icopia-14.2015.37
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Magnetcic Field on the Phase Transition of Swollen Liquid Crystal Elastomers

Abstract: The effect of magnetic fields on the swelling of liquid crystal elastomers (LCE) dissolved in liquid crystal (LC) solvent have been studied. The Flory-Huggins model used to calculate the free energy of an isotropic mixing and the Maier-Saupe model used to calculate the free energy of a nematic mixing. Numerical integration method used to calculate the order parameter and the total free energy of system (consists of : nematic free energy, elastic free energy, isotropic mixing free energy and magnetic free energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Chemically, it is composed of a lightly crosslinked siloxane chain and the rigid, anisotropic mesogens which are covalently bound to the crosslinked siloxane chain. Therefore, LCE combines the elasticity properties of long polymeric chains with the orientational order of liquid crystal mesogens, which results in novel responses to external fields, such as thermal [9], electric [10,11], light [12,13], magnetic [14] and chemical [15] etc. These responses are fast [16] and reversible [17], leading to prospective applications like artificial muscle [18], remote controllable implement [19,20], actuators and sensors [21,22], energy harvester [2] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, it is composed of a lightly crosslinked siloxane chain and the rigid, anisotropic mesogens which are covalently bound to the crosslinked siloxane chain. Therefore, LCE combines the elasticity properties of long polymeric chains with the orientational order of liquid crystal mesogens, which results in novel responses to external fields, such as thermal [9], electric [10,11], light [12,13], magnetic [14] and chemical [15] etc. These responses are fast [16] and reversible [17], leading to prospective applications like artificial muscle [18], remote controllable implement [19,20], actuators and sensors [21,22], energy harvester [2] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is a coupling between the mechanical deformation and the director, the orientational order will directly induce the shape variation of nematic elastomers [6]. Experiments have shown that the orientation order can be manipulated by electrical field [7], light [8], thermal [9], magnetic field [10], etc, and its response to external fields are fast and reversible. This unique perfomance of nematic elastomer has made it widely applied in artificial muscles [11], remote controllable implements and actuators [12,13], motors, sensors [14], and tunable optical devices [15].…”
Section: Introductionmentioning
confidence: 99%